Feasibility of ramming erosion area of earthen sites using solidified soil induced by an ancient curing Agent, calcined ginger nuts. (17th March 2023) - Peng, Erxing; Li, Dandan; Hu, Xiaoying; Sheng, Yu; Chou, Yaling; Cao, Wei; Chen, Ji; Li, Qifeng
Highlights: Weatherability of soil can be effectively improved by CGN. The strength of solidified samples slightly increased with the dosage and curing time. Under the appropriate dosage, color difference of solidified samples can meet principle of "repairing the old as the old". Carbonation is the dominant reaction of CGN during the curing stage. Abstract: Earthen site is a kind of preciously historic building constructed with soil as the building material. In northwestern China, the earthen sites are threatened because of environmental hazards, such as wind erosion, water erosion, and so on. Rammed reinforcement of the erosion area can improve the overall stability of the site. In addition, region formed by ramming reinforcement can be defined as ramming area. The formation of the ramming area is a new surface, and new interface between the ramming area and the original site is formed. Therefore, ramming area must meet principle of "repairing the old as the old" and maintain compatibility with the original earthen sites in terms of soil strength, permeability. Calcined ginger nuts is an environment-friendly and inorganic material that is emerging curing agent to reinforce the erosion area of the earthen site, which may make the reinforcement area to meet the above requirements. A series of tests were performed to verify its feasibility and investigate its solidified effects and mechanism. The study demonstrated that, with dosage and curing time increasing, the shear strength and unconfined compressive strength of solidified samples slightly improved and the permeability coefficient decreased with a small extent, the disintegration and shrinkage rate significantly decreased, and the total color difference value of samples increased as the sample became brighter. Furthermore, the mechanism of solidified soil has been studied by performing mercury injection, X-ray diffraction, and scanning electron micrograph tests under 25% dosage, which is proposed as the optimum dosage. The pore size decreased with increase of curing time as calcium carbonate content increased. Crystal type of calcium carbonate is mainly calcite—a material with high strength and cohesiveness. Thus, carbonation is the dominant reaction during the curing stage. Moreover, the crystal morphology of calcite changes from needle-stick calcite to flake. In conclusion, calcined ginger nuts can be used as curing agent for reinforcing the erosion area of earthen sites.